Relationship between preoperative body composition parameters and postoperative clinical score for rotator cuff tear patients - Naoki Takatori, MD, PhD; Yoshiyasu Uchiyama, MD, PhD; Takeshi Imai, MD, PhD; Shiho Wasai, MD, PhD; Masahiko Watanabe, MD, PhD (JSES International, 2025)
Background: Various intrinsic and extrinsic factors have been reported for rotator cuff tears (RCTs). This study aimed to assess the relationship between preoperative body composition parameters and postoperative clinical score in patients who underwent surgery for RCT. Methods: The participants in this study were 42 patients (42 shoulders; 33 men, 9 women) who underwent preoperative measurement of body composition and were then evaluated 1 year after surgical rotator cuff repair. Mean age at the time of examination was 61 years. Clinical outcomes were quantified using the Constant–Murley score, then patients were divided into an excellent group (Group E; Constant–Murley score ≥80) and a failure group (Group F; Constant–Murley score ≤79). Patient's background characteristics, preoperative physical findings, and body composition parameters were compared between Groups E and F. Results: Appendicular skeletal muscle mass (SMM) index of the upper limb on the affected side and phase angle were significantly higher in Group E (appendicular SMM index: Group E 0.50 ± 0.11 kg/m2, Group F 0.42 ± 0.12 kg/m2, P = .027; phase angle: Group E 5.41° ± 0.62°, Group F 4.98° ± 0.51°, P = .032) and showed significant positive correlations with the clinical score (appendicular SMM index: P = .002, r = 0.474; phase angle: P = .001, r = 0.490). Conversely, the ratio of extracellular water to total body water was significantly higher in Group F (Group E 42.95% ± 2.58%, Group F 44.69% ± 3.02%; P = .031) and showed a significant negative correlation with the clinical score (P = .005, r = −0.426). Conclusion: A relationship between RCT and whole-body condition has been reported but no reports have clarified the relationships between body composition parameters and clinical score for patients with RCTs. Relationships between preoperative body composition parameters and postoperative clinical score were investigated in patients with RCTs. The group with better preoperative body composition parameters showed significantly better postoperative clinical score. Moreover, the postoperative clinical score correlated positively with the appendicular SMM index and phase angle and negatively with extracellular water/total body water. These findings suggest that measuring body composition preoperatively may provide predictors of postoperative clinical score in patients with RCTs.